2004
DOI: 10.1029/2003gl018855
|View full text |Cite
|
Sign up to set email alerts
|

CLUSTER observations of lower hybrid waves excited at high altitudes by electromagnetic whistler mode signals from the HAARP facility

Abstract: We report new observations from the CLUSTER spacecraft of strong excitation of lower hybrid (LH) waves by electromagnetic (EM) whistler mode waves at altitudes ≥20,000 km outside the plasmasphere. Previous observations of this phenomenon occurred at altitudes ≤7000 km. The excitation mechanism appears to be linear mode coupling in the presence of small scale plasma density irregularities. These observations provide strong evidence that EM whistler mode waves are continuously transformed into LH waves as the wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…Closer examination of the detected pulses shows that at both frequencies there actually are two pulses roughly centered close to the nominal frequency, separated in frequency by approximately 25 Hz. These sideband waves have been interpreted as being lower hybrid (LH) waves possibly generated through linear mode coupling in the presence of small-scale plasma density irregularities (Bell and Ngo, 1990;Bell et al, 2004).…”
Section: Simulation Results: the Ray-tracing Techniquementioning
confidence: 99%
“…Closer examination of the detected pulses shows that at both frequencies there actually are two pulses roughly centered close to the nominal frequency, separated in frequency by approximately 25 Hz. These sideband waves have been interpreted as being lower hybrid (LH) waves possibly generated through linear mode coupling in the presence of small-scale plasma density irregularities (Bell and Ngo, 1990;Bell et al, 2004).…”
Section: Simulation Results: the Ray-tracing Techniquementioning
confidence: 99%
“…Here, although it is possible that whistler waves may be scattering off plasma density variations and converting into lower hybrid fluctuations [21][22][23], the anomalous resistivity associated with the lower hybrid waves is still found to be small; η ∼ 10 −3 Ωm [24]. Given a cross tail current density of ∼ 10 −8 Am −2 , this corresponds to an electric field of ∼ 0.01mV m −1 , (< 1% of the reconnection electric field) meaning that any modification to the overall reconnection rate is negligible.…”
mentioning
confidence: 99%
“…Supported by simultaneous Waves of High frequency and Sounder for Probing of Electron density by Relaxation (WHISPER) observations of electron density, the Platino et al [2005] study presents evidence that whistlers are observed in the low-density regions outside the plasmasphere only in the presence of large-scale irregularities within which the wave can be ducted. Furthermore, Platino et al [2005] argue that the Cluster observations of lightning-generated whistlers outside the plasmasphere support the theory of the loss of the electrostatic whistler mode energy via mode conversion to quasi-static lower hybrid waves [Bell and Ngo, 1990;Bell et al, 2004]. This work will place the Cluster-observed whistlers presented by Platino et al [2005] into a global context with respect to the plasmasphere/plasmapause itself by employing the near-real-time monitoring of the global structure and dynamics of Earth's plasmasphere provided by the Extreme Ultraviolet Imager (EUV) imager aboard the Imager for Magnetopause-to-Aurora Global Exploration (IMAGE) satellite.…”
Section: Introductionmentioning
confidence: 78%
“…We then conclude this report with a discussion in section 4 of the implications that these associated Cluster/EUV observations have for the whistler wave propagation beyond the plasmasphere, whistler mode conversion theory as proposed by Bell et al [2004] and the potential consequences for radiation belt populations exposed to these escaping lightning-generated whistler waves. More to the point, we argue that the density irregularities necessary for the ducting of lighting-generated whistlers to locations outside of the plasmasphere are a direct consequence of the localized-and perhaps filamentary-inner magnetospheric electric fields responsible for the formation of these larger-scale plasmaspheric features and lower latitude access to ducting channels afforded sferics by the formation of these features.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation